IL-32α-induced inflammation constitutes a link between obesity and colon cancer. (3rd July 2017) - Catalán, Victoria; Gómez-Ambrosi, Javier; Rodríguez, Amaia; Ramírez, Beatriz; Ortega, Victor A.; Hernández-Lizoain, José Luis; Baixauli, Jorge; Becerril, Sara; Rotellar, Fernando; Valentí, Víctor; Moncada, Rafael; Silva, Camilo; et al.
ABSTRACT: Growing evidence indicates that adipose tissue inflammation is an important mechanism whereby obesity promotes cancer risk and progression. Since IL-32 is an important inflammatory and remodeling factor in obesity and is also related to colon cancer (CC) development, the aim of this study was to explore whether IL-32 could function as an inflammatory factor in human obesity-associated CC promoting a microenvironment favorable for tumor growth. Samples obtained from 84 subjects [27 lean (LN) and 57 obese (OB)] were used in the study. Enrolled subjects were further subclassified according to the established diagnostic protocol for CC (49 without CC and 35 with CC). We show, for the first time, that obesity ( p = 0.009) and CC ( p = 0.026) increase circulating concentrations of IL-32α. Consistently, we further showed that gene ( p < 0.05) and protein ( p < 0.01) expression levels of IL-32α were upregulated in VAT from obese patients with CC. Additionally, we revealed that IL32 expression levels are enhanced by hypoxia and inflammation-related factors in HT-29 CC cells as well as that IL-32α is involved in the upregulation of inflammation ( IL8, TNF, and CCL2 ) and extracellular matrix (ECM) remodeling ( SPP1 and MMP9 ) genes in HT-29 cancer cells. Additionally, we also demonstrate that the adipocyte-conditioned medium obtained from obese patients stimulates ( p < 0.05) the expression of IL32 in human CC cells. These findings provide evidence of the potential involvement of IL-32 in the development of obesity-associated CC as a pro-inflammatory and ECM remodeling cytokine.